The invisible college of cluster research: a bibliometric core–periphery analysis of the literature. Issue 5 (27th May 2020) - Sedita, S.R.; Caloffi, A.; Lazzeretti, L.
ABSTRACT: This paper explores the evolutionary trajectories of cluster research, building upon the sociology of science concept of the invisible college, and it undertakes a core–periphery analysis of the literature. We build a database that includes 8, 381 articles, collected from Web of Science, that cite the foundational works of cluster research, and we perform a longitudinal analysis of its evolution from 1985 onward, identifying the core and periphery, in terms of keywords and concepts, for each period (six-year window). We find evidence that cluster research has a core–periphery structure. Literature develops thanks to new inputs from the periphery, which increases over time as the core progressively shrinks. The periphery becomes fragmented and is characterised by subgroups of small communities. Drawing on the metaphor of the invisible college, we argue that this evolutionary trajectory is not exclusive of the cluster but might possibly characterise other scientific concepts.